2022
DOI: 10.3389/fonc.2022.762906
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Selection of Imaging Examination for Lymph Node Detection of Breast Cancer With Different Molecular Subtypes

Abstract: ObjectiveAxillary lymph node management is an important part of breast cancer surgery and the accuracy of preoperative imaging evaluation can provide adequate information to guide operation. Different molecular subtypes of breast cancer have distinct imaging characteristics. This article was aimed to evaluate the predictive ability of imaging methods in accessing the status of axillary lymph node in different molecular subtypes.MethodsA total of 2,340 patients diagnosed with primary invasive breast cancer afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Zheng et al study showed that ER/PR+ HER2− patients using both the ultrasonography method and magnetic resonance imaging (MRI) is more valuable in diagnosing the disease. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al study showed that ER/PR+ HER2− patients using both the ultrasonography method and magnetic resonance imaging (MRI) is more valuable in diagnosing the disease. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al study showed that ER/PR+ HER2− patients using both the ultrasonography method and magnetic resonance imaging (MRI) is more valuable in diagnosing the disease. 26,27 MRI is another important diagnostic tool that can be used for monitoring the response to the treatment, high-risk patients, and detection of metastasis 7,26 But MRI is used in complex cases because of the cost problem in our country.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the SN technique is even less reliable in patients with axillary lymph node involvement and a more proliferative breast cancer, which is therefore more aggressive. Future trials should analyze all the techniques available to quantify axillary tumor load considering the histopathological, immunohistochemical and molecular characteristics of the tumors, given that it has been proven that these features influence the axillary tumor load (24,25) and the accuracy of diagnostic tests (26,27) An obvious limitation of this initial phase of the MUTAS trial is the very small number of patients analyzed that did not reach the predefined estimated sample size. The reason for the low recruitment was the outbreak of the COVID 2019 (COVID-19) pandemic a few months after the start of the study, 2.5 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned before, LN disease will be underestimated in up to 30% patients with conventional US, with detrimental effects on clinical care and clinical decision-making. It is safe to assume that even if a large proportion of these patients meet the Z0011 criteria (21,43), a significative proportion with positive LNs may be misclassified as having EBC, missing the chance for neoadjuvant medical therapy prior to surgery (44,45).…”
Section: Discussionmentioning
confidence: 99%